Синтез багатовимірних координуючих систем керування з різнотемповою дискретизацією в детермінованому середовищі - Romanenko, V. D.; Milyavsky, Y. L. (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2011)
The control problem of relations between the output coordinates of the multidimensional multirate objects in deterministic environment is formulated and solved. A new control algorithm that ensures simultaneous fulfillment of both monitoring and coordinating problems in transient and steady states is proposed. The results of numerical simulation, confirming the practical significance of this development are shown.